Electrode plate, preparation method thereof and lithium ion battery
By using electrode slurry containing polymer monomers to prepare electrode sheets, the problem of poor compatibility between gel electrolyte and battery sheets in lithium-ion batteries is solved, and the electrochemical performance and mechanical strength of the battery are significantly improved.
Patent Information
- Application Number
- CN202411947139.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-29
AI Technical Summary
The interface compatibility between the gel electrolyte and the battery pole in lithium-ion batteries is poor, affecting the electrochemical performance of the battery.
The electrode sheet is prepared by providing an electrode slurry, including an active substance, a gel agent and a first solvent, wherein the gel agent comprises a polymer monomer and coated on the current collector, and heat-cured to prepare the electrode sheet. This method improves interface compatibility and ion transport efficiency between the gel polymer and the electrode active material.
The electrochemical performance of the battery is improved, the interface impedance between the gel polymer and the electrode active substance is reduced, and the mechanical strength and stability of the electrode sheet are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrode plate and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries with high energy density, high power density, long life and no memory are being widely used in smart homes, smart wearables, smart communication tools, the Internet of Everything and other scenarios. The traditional manufacturing process of lithium-ion batteries is generally as follows: first, a mixture of active material, conductive agent and binder is coated on the current collector, and then the electrode plate is obtained after rolling, die-cutting and other processes, and then the electrode plate and polyolefin separator are stacked or wound to obtain a battery cell, and finally the electrolyte is injected into the battery cell, and the gelling agent in the electrolyte infiltrates the electrode plate and then solidifies in situ in the battery cell to form a gel electrolyte.
[0003] In the related art, when preparing lithium-ion batteries, the electrolyte does not wet the battery cell pole pieces well, resulting in poor interface compatibility between the gel electrolyte formed after in-situ curing and the battery pole pieces, which affects the electrochemical performance of the battery. Summary of the invention
[0004] The embodiments of the present application provide an electrode plate and a method for preparing the same, and a lithium-ion battery, which can improve the technical problem that the interface compatibility between the gel electrolyte and the battery plate is poor, affecting the electrochemical performance of the battery.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing an electrode sheet, the method for preparing an electrode sheet comprising the following steps:
[0006] Providing an electrode slurry, wherein the electrode slurry comprises an active material, a gelling agent and a first solvent, wherein the gelling agent comprises a polymer monomer;
[0007] The electrode slurry is coated on a current collector and heated and cured to obtain the electrode plate.
[0008] In one embodiment, the method for preparing the electrode slurry comprises the following steps:
[0009] The active material, the gelling agent, the first solvent and other raw materials in the formulated amount are uniformly mixed to obtain the electrode slurry.
[0010] In one embodiment, the mixing is stirring mixing, and / or the ambient temperature of the mixing is 20° C.-30° C., and / or the ambient humidity of the mixing is less than or equal to 10%, and / or the mixing time is 4h-20h, and / or the mixing is wet mixing; and / or
[0011] The electrode slurry is coated on the current collector by an extrusion coater; and / or
[0012] The temperature of the heating and curing is 60° C.-150° C., and / or the time of the heating and curing is 20 min-60 min.
[0013] In one embodiment, the other raw materials include a conductive agent and an initiator; and / or
[0014] The gelling agent further comprises a cross-linking agent and a plasticizer; and / or
[0015] The electrode plate is a positive electrode plate, the active material includes at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt manganese oxide, and / or the current collector includes at least one of aluminum foil and stainless steel foil; and / or
[0016] The electrode plate is a negative electrode plate, the active material includes at least one of graphite, silicon carbon, lithium carbonate, and carbon nanotubes, and / or the current collector includes at least one of copper foil and stainless steel foil; and / or
[0017] The polymer monomer comprises at least one of polyethylene glycol dimethacrylate, triethylene glycol dimethacrylate, poly(ethylene glycol) diacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, ethylene glycol phenyl ether acrylate, methyl methacrylate, vinyl ethylene carbonate, poly(ethylene glycol), polyvinylidene fluoride, poly(vinylidene fluoride-co-hexafluoropropylene), and polyacrylonitrile; and / or
[0018] The first solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethylacetamide, acetonitrile, dimethyl sulfoxide, and tetrahydrofuran.
[0019] In one embodiment, the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the first solvent is (35-50): (0.05-3): (0.5-10): (0.005-0.3): (35-70); and / or
[0020] The mass ratio of the polymer monomer, the cross-linking agent and the plasticizer is (20-90): (5-50): (1-20).
[0021] In one embodiment, the conductive agent includes at least one of carbon black, carbon nanotubes, and graphene; and / or
[0022] The initiator comprises at least one of N,N-azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, diethylhexyl oxydicarbonate, benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate; and / or
[0023] The cross-linking agent comprises at least one of pentaerythritol tetraacrylate, polyethylene glycol dimethacrylate, triethylene glycol dimethacrylate, poly(ethylene glycol) diacrylate, trimethylol propane ethoxylate triacrylate, propoxylated trimethylol propane triacrylate, trimethylol propane trimethacrylate, and di(trimethylol propane) tetraacrylate; and / or
[0024] The plasticizer includes at least one of succinonitrile, adiponitrile, methylglutaronitrile, 3-methoxypropionitrile, vinylene carbonate, 4-vinyl-1,3-dioxolane-2-one, silicon dioxide and titanium dioxide.
[0025] In a second aspect, an embodiment of the present application provides an electrode plate, which is prepared by the preparation method described above.
[0026] In one embodiment, the electrode plate includes a current collector and a composite gel layer, wherein the composite gel layer is formed on the surface of the current collector by in-situ polymerization of polymer monomers, wherein the composite gel layer includes a gel polymer and an active substance dispersed in the gel polymer; and / or
[0027] The thickness of the electrode plate is 20 μm-500 μm; and / or
[0028] The electrode plate is a positive electrode plate, the active material includes at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt manganese oxide, and / or the current collector includes at least one of aluminum foil and stainless steel foil; and / or
[0029] The electrode plate is a negative electrode plate, the active material includes at least one of graphite, silicon carbon, lithium carbonate, and carbon nanotubes, and / or the current collector includes at least one of copper foil and stainless steel foil.
[0030] In a third aspect, an embodiment of the present application provides a lithium-ion battery, comprising the electrode plate as described above or the electrode plate prepared by the preparation method as described above.
[0031] In a fourth aspect, an embodiment of the present application provides a method for preparing a lithium ion battery, comprising the following steps:
[0032] Providing an electrode plate, a separator and an electrolyte, wherein the electrode plate is prepared by the preparation method described above;
[0033] The electrode plates and the separator are stacked or wound to obtain a battery cell;
[0034] The battery cell is installed in a battery casing, the electrolyte is injected into the battery cell, and the battery cell is sealed to obtain the lithium ion battery.
[0035] In one embodiment, the mass percentage of the electrolyte in the lithium-ion battery is 10%-18%; and / or
[0036] The electrolyte comprises a second solvent, a lithium salt and an additive; and / or
[0037] The electrode plates include a positive electrode plate and a negative electrode plate. The positive electrode plate, the separator and the negative electrode plate are stacked in sequence to obtain the battery cell.
[0038] In one embodiment, the second solvent comprises at least one of ethylene carbonate, propylene carbonate, vinyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dimethyltetrahydrofuran, tetrahydrofuran, 1,2-dimethoxyethane, ethyl acetate, methyl acetate, methyl formate, ethyl formate, propyl formate, isopropyl formate, and 1,4-butyrolactone; and / or
[0039] The lithium salt comprises at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluorooxalatophosphate, lithium bis(fluorobis(oxalatophosphate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, and lithium bis(oxalatoborate); and / or
[0040] The additive comprises at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, vinyl sulfite, polyether sulfone, vinyl sulfate, and propenyl-1,3-sultone; and / or
[0041] The molar concentration of the lithium salt in the electrolyte is 1.2 mol / L-2.0 mol / L; and / or
[0042] The mass percentage of the second solvent in the electrolyte is 50%-75%; and / or
[0043] The mass percentage of the lithium salt in the electrolyte is 10%-35%; and / or
[0044] The mass percentage of the additive in the electrolyte is 1%-15%.
[0045] Beneficial effects of the embodiments of the present application:
[0046] In the embodiment of the present application, when preparing the electrode plate, an electrode slurry is first provided, the electrode slurry includes an active material, a gelling agent and a first solvent, and the gelling agent includes a polymer monomer; then the electrode slurry is coated on the current collector, heated and cured, and the electrode plate is obtained. On the one hand, compared with the traditional electrolyte infiltration of the electrode plate by standing, the electrode active material in the present application is directly in contact with the gelling agent, and when the polymer monomer is heated and cured to form a gel polymer, the gel polymer can wrap the active material particles, and the active material particles are directly in contact with the gel polymer and evenly dispersed in the gel polymer, which can improve the interface compatibility between the gel polymer and the electrode active material, reduce the interface impedance between the gel polymer and the electrode active material, and improve the electrochemical performance of the battery. At the same time, the gel polymer can provide an ion transmission channel for the electrode plate, which is beneficial to improve the ion transmission efficiency. On the other hand, the electrode slurry is directly cured in situ on the current collector to form a gel polymer, which can improve the adhesion between the gel polymer and the current collector, reduce the risk of the gel polymer falling off the current collector, and improve the stability of the electrode plate structure. At the same time, the gel polymer can provide a skeleton support for the electrode plate to ensure the mechanical strength of the electrode plate. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state; while "inside" and "outside" refer to the outline of the device.
[0048] In the related art, the interface compatibility between the gel electrolyte and the battery electrode is poor, which affects the electrochemical performance of the battery and needs to be further improved.
[0049] To solve the above problems, the present invention provides a method for preparing an electrode sheet, comprising the following steps:
[0050] S11. Providing electrode slurry, wherein the electrode slurry includes an active material, a gelling agent and a first solvent, and the gelling agent includes a polymer monomer.
[0051] S12, coating the electrode slurry on the current collector, heating and curing, and obtaining an electrode plate.
[0052] In this embodiment, when preparing the electrode plate, an electrode slurry is first provided, the electrode slurry includes an active material, a gelling agent and a first solvent, and the gelling agent includes a polymer monomer; then the electrode slurry is coated on the current collector, heated and cured, and the electrode plate is obtained. On the one hand, compared with the conventional electrolyte solution that infiltrates the electrode plate by standing, the electrode active material in the present application is directly in contact with the gelling agent, and when the polymer monomer in the gelling agent is heated and cured to form a gel polymer, the gel polymer can wrap the active material particles, and the active material particles are directly in contact with the gel polymer and evenly dispersed in the gel polymer, which can improve the interface compatibility between the gel polymer and the electrode active material, reduce the interface impedance between the gel polymer and the electrode active material, and improve the electrochemical performance of the battery. At the same time, the gel polymer can provide an ion transmission channel for the electrode plate, which is beneficial to improve the ion transmission efficiency. On the other hand, the electrode slurry is directly cured in situ on the current collector to form a gel polymer, which can improve the adhesion between the gel polymer and the current collector, reduce the risk of the gel polymer falling off the current collector, and improve the stability of the electrode plate structure. At the same time, the gel polymer can provide a skeleton support for the electrode plate to ensure the mechanical strength of the electrode plate.
[0053] In one embodiment, the method for preparing the electrode slurry comprises the following steps:
[0054] S111, uniformly mixing the active material, gelling agent, first solvent and other raw materials in the formulated amounts to obtain electrode slurry.
[0055] In one embodiment, in step S111, the mixing is stirring mixing, the mixing environment temperature is 20°C-30°C, and the mixing time is 4h-20h. Optionally, the mixing environment temperature can be any one of 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, etc., or a range between any two thereof; the mixing time can be any one of 4h, 8h, 10h, 14h, 18h, 20h, etc., or a range between any two thereof.
[0056] In one embodiment, in step S111, the mixed environmental humidity is less than or equal to 10%. In the traditional electrode preparation process, generally, the electrode active material, electrolyte, conductive agent, gelling agent and other raw materials are first stirred and mixed to obtain slurry, and then the slurry is coated on the current collector, and then the electrode is prepared after rolling, drying, sheeting and assembly. Since the electrolyte contains lithium salt, the slurry stirring, coating, rolling, drying, sheeting and assembly, packaging and other processes need to be carried out under the condition of environmental humidity below 0.1% to prevent water in the air from reacting with lithium salt in the electrolyte to generate corrosive hydrofluoric acid. The preparation of the battery has high requirements for environmental humidity and high humidity control cost; in addition, the solvent in the electrolyte is easy to volatilize during the drying process, affecting the performance of the battery; in this embodiment, in the preparation process of the electrode, the raw materials for the preparation of the electrode do not contain electrolyte, therefore, the mixed environmental humidity is less than or equal to 10%, the requirements for environmental humidity are relatively low, and the humidity control cost can be reduced. Optionally, the mixed ambient humidity may be any one of 1%, 3%, 5%, 7%, 9%, 10%, etc., or a range between any two of them.
[0057] In one embodiment, in step S12, the electrode slurry can be coated on the current collector by roller coating, blade coating, extrusion coating, etc., which are not limited here. Optionally, the electrode slurry is coated on the current collector by an extrusion coater.
[0058] In one embodiment, in step S12, the temperature of heating and curing is 60°C-150°C, and the time of heating and curing is 20min-60min. Optionally, the temperature of heating and curing can be any one of 60°C, 80°C, 90°C, 100°C, 130°C, 150°C, etc., or a range between any two thereof; the time of heating and curing can be any one of 20min, 30min, 40min, 50min, 60min, etc., or a range between any two thereof. In this embodiment, if the temperature of heating and curing is too low, it is easy to cause the reaction rate and conversion rate of the gelling agent to be reduced when heating and curing to generate a gel polymer, and the molecular weight of the generated gel polymer is too low, affecting the mechanical properties of the gel polymer; if the temperature of heating and curing is too high, it is easy to cause the polymerization reaction of the gelling agent to be too fast and cause an explosion.
[0059] In one embodiment, the polymer monomer includes at least one of polyethylene glycol dimethacrylate, triethylene glycol dimethacrylate, poly(ethylene glycol) diacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, ethylene glycol phenyl ether acrylate, methyl methacrylate, vinyl ethylene carbonate, poly(ethylene glycol), polyvinylidene fluoride, poly(vinylidene fluoride-co-hexafluoropropylene), and polyacrylonitrile.
[0060] In one embodiment, the first solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethylacetamide, acetonitrile, dimethyl sulfoxide, and tetrahydrofuran.
[0061] In one embodiment, the electrode plate is a positive electrode plate, the active material includes at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt manganese oxide, and the current collector includes at least one of aluminum foil and stainless steel foil.
[0062] In one embodiment, the electrode plate is a negative electrode plate, the active material includes at least one of graphite, silicon carbon, lithium carbonate, and carbon nanotubes, and the current collector includes at least one of copper foil and stainless steel foil.
[0063] In one embodiment, the other raw materials include a conductive agent. In this embodiment, the conductive agent can promote the transmission rate of lithium ions in the gel polymer, improve the ionic conductivity of the gel polymer, and at the same time, increase the mechanical strength of the gel polymer, and increase the anti-extrusion performance, anti-heavy impact performance and needle puncture performance of the electrode plate. Optionally, the conductive agent includes at least one of carbon black, carbon nanotubes, and graphene.
[0064] In one embodiment, the other raw materials also include an initiator. In this embodiment, the initiator can initiate a polymerization reaction of the polymer monomer, thereby improving the efficiency and conversion rate of the polymerization reaction. Optionally, the initiator includes at least one of N,N-azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, diethylhexyl oxydicarbonate, benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate.
[0065] In one embodiment, the gelling agent further includes a cross-linking agent. The cross-linking agent can increase the cross-linking degree of the gel polymer, improve the yield strength and tensile strength of the gel polymer, and thus improve the safety performance of the electrode plate. Optionally, the cross-linking agent includes at least one of pentaerythritol tetraacrylate, polyethylene glycol dimethacrylate, triethylene glycol dimethacrylate, poly(ethylene glycol) diacrylate, trimethylol propane ethoxylate triacrylate, propoxylated trimethylol propane triacrylate, trimethylol propane trimethacrylate, and di(trimethylol propane) tetraacrylate.
[0066] In one embodiment, the gelling agent further includes a plasticizer. The plasticizer can adjust the viscosity of the electrode slurry so that the electrode slurry can be smoothly coated on the current collector, thereby improving the efficiency of production and processing. Optionally, the plasticizer includes at least one of succinonitrile, adiponitrile, methyl glutaronitrile, 3-methoxypropionitrile, vinylene carbonate, 4-vinyl-1,3-dioxolane-2-one, silicon dioxide, and titanium dioxide.
[0067] In one embodiment, the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the first solvent is (35-50): (0.05-3): (0.5-10): (0.005-0.3): (35-70). In this embodiment, the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the first solvent is controlled within the above range, so that the electrode plate has a larger energy density and a higher ion transmission efficiency, and at the same time, the electrode plate has a higher self-supporting force.
[0068] Optionally, the mass ratio between the active substance, the conductive agent, the gelling agent, the initiator and the first solvent can be any one of (35:0.05:0.5:0.005:35), (45:1.5:5:0.2:55), (35:0.05:0.5:0.005:70), (50:3:10:0.3:30), (50:3:0.5:0.3:70), (35:0.05:10:0.005:35), (50:3:10:0.3:70), etc., or a range between any two of them.
[0069] In one embodiment, the mass ratio of the polymer monomer, the cross-linking agent and the plasticizer is (20-90): (5-50): (1-20). In this embodiment, the mass ratio of the polymer monomer, the cross-linking agent and the plasticizer is controlled within the above range, so that the generated gel polymer has appropriate mechanical strength and can provide support for the electrode plate. At the same time, the gel polymer can tightly adhere the active material to the current collector, reducing the problem of material drop and dispersion of the electrode plate.
[0070] Optionally, the mass ratio between the polymer monomer, the cross-linking agent and the plasticizer can be any one of (20:5:1), (20:5:20), (60:25:10), (90:50:20), (90:5:1), (20:50:20), (90:50:1), etc., or a range between any two of them.
[0071] The present application also provides an electrode plate, which is prepared by the preparation method described above.
[0072] In one embodiment, the electrode plate includes a current collector and a composite gel layer, the composite gel layer is formed on the surface of the current collector by an in-situ polymerization method of a polymer monomer, wherein the composite gel layer includes a gel polymer and an active substance dispersed in the gel polymer. In this embodiment, the gel polymer in the electrode plate can wrap the active substance particles, the active substance particles directly contact the gel polymer and are evenly dispersed in the gel polymer, which can improve the interface compatibility between the gel polymer and the electrode active substance, reduce the interface impedance between the gel polymer and the electrode active substance, and improve the electrochemical performance of the battery. At the same time, the gel polymer can provide an ion transmission channel for the electrode plate, which is conducive to improving the ion transmission efficiency; in addition, the polymer monomer is directly in-situ cured on the current collector to form a gel polymer, which can improve the adhesion between the gel polymer and the current collector, reduce the risk of the gel polymer falling off the current collector, and improve the stability of the electrode plate structure. At the same time, the gel polymer can provide a skeleton support for the electrode plate to ensure the mechanical strength of the electrode plate.
[0073] In one embodiment, the thickness of the electrode plate is 20μm-500μm. In this embodiment, if the thickness of the electrode plate is too small, it is easy to cause the electrode plate to be too thin, the self-supporting effect of the electrode plate is not ideal, and the plate is easy to be disconnected in the later production process; if the thickness of the electrode plate is too large, it is easy to cause the transmission path of electrons and lithium ions to be too long during the operation of the battery cell, increase the polarization of the battery cell, and reduce the rate discharge performance of the battery cell. Optionally, the thickness of the electrode plate can be any one of 20μm, 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm, 500μm, etc., or a range between any two.
[0074] In one embodiment, the electrode plate is a positive electrode plate, the active material includes at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt manganese oxide, and the current collector includes at least one of aluminum foil and stainless steel foil.
[0075] In one embodiment, the electrode plate is a negative electrode plate, the active material includes at least one of graphite, silicon carbon, lithium carbonate, and carbon nanotubes, and the current collector includes at least one of copper foil and stainless steel foil.
[0076] The present application also provides a lithium-ion battery, including the electrode plate as described above or the electrode plate prepared by the preparation method as described above. In this embodiment, the interface compatibility between the gel polymer in the electrode plate and the electrode active material is good, which can reduce the interface impedance between the gel polymer and the electrode active material and improve the electrochemical performance of the battery.
[0077] In this embodiment, the type of lithium-ion battery is not limited, and the lithium-ion battery can be one of a ternary soft-pack battery, a ternary steel-shell battery, a lithium cobalt oxide soft-pack battery, and a lithium cobalt oxide steel-shell battery.
[0078] The present application also provides a method for preparing a lithium ion battery, comprising the following steps:
[0079] S21, providing an electrode plate, a diaphragm and an electrolyte, wherein the electrode plate is the electrode plate as described above or an electrode plate prepared by the preparation method as described above;
[0080] S22, stacking or winding the electrode plates and the diaphragm to obtain a battery cell;
[0081] S23, placing the battery cell into a battery casing, injecting electrolyte into the battery cell, and sealing the battery cell to obtain a lithium-ion battery.
[0082] In this embodiment, the electrode plate has a composite gel layer, which includes a gel polymer and an active substance dispersed in the gel polymer. The gel polymer in the electrode plate can wrap the active substance particles. The active substance particles are in direct contact with the gel polymer and are evenly dispersed in the gel polymer. This can improve the interface compatibility between the gel polymer and the electrode active substance, reduce the interface impedance between the gel polymer and the electrode active substance, and improve the electrochemical performance of the battery. At the same time, the gel polymer can provide an ion transmission channel for the electrolyte, which is beneficial to improving the ion transmission efficiency.
[0083] In one embodiment, the electrode plates include a positive electrode plate and a negative electrode plate, and the positive electrode plate, the separator and the negative electrode plate are stacked in sequence to manufacture a battery cell.
[0084] In one embodiment, the mass percentage of the electrolyte in the lithium ion battery is 10%-18%. Optionally, the mass percentage of the electrolyte in the lithium ion battery can be any one of 10%, 12%, 14%, 16%, 18%, etc. or a range between any two.
[0085] In one embodiment, the electrolyte includes a second solvent, a lithium salt and an additive.
[0086] In one embodiment, the second solvent includes at least one of ethylene carbonate, propylene carbonate, vinyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dimethyltetrahydrofuran, tetrahydrofuran, 1,2-dimethoxyethane, ethyl acetate, methyl acetate, methyl formate, ethyl formate, propyl formate, isopropyl formate, and 1,4-butyrolactone.
[0087] In one embodiment, the mass percentage of the second solvent in the electrolyte is 50%-75%. Optionally, the mass percentage of the second solvent in the electrolyte can be any one of 50%, 55%, 60%, 65%, 70%, 75%, etc. or a range between any two.
[0088] In one embodiment, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluorooxalatophosphate, lithium bis(fluorobis(oxalatophosphate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, and lithium bis(oxalatoborate).
[0089] In one embodiment, the mass percentage of the lithium salt in the electrolyte is 10%-35%. Optionally, the mass percentage of the lithium salt in the electrolyte can be any one of 10%, 15%, 20%, 25%, 30%, 35%, etc. or a range between any two.
[0090] In one embodiment, the molar concentration of the lithium salt in the electrolyte is 1.2mol / L-2.0mol / L. Optionally, the molar concentration of the lithium salt in the electrolyte can be any one of 1.2mol / L, 1.4mol / L, 1.6mol / L, 1.8mol / L, 2.0mol / L, etc., or a range between any two. In this embodiment, if the concentration of the lithium salt in the electrolyte is too small, it is easy to cause insufficient lithium salt content, affecting the cycle performance and rate performance of the battery cell. If the concentration of the lithium salt in the electrolyte is too high, it is easy to cause the viscosity of the electrolyte to be too high, and the effect of the electrolyte infiltrating the battery cell is not ideal.
[0091] In one embodiment, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, vinyl sulfite, polyether sulfone, vinyl sulfate, and propenyl-1,3-sultone.
[0092] In one embodiment, the mass percentage of the additive in the electrolyte is 1%-15%. Optionally, the mass percentage of the additive in the electrolyte can be any one of 1%, 3%, 5%, 7%, 10%, 13%, 15%, etc., or a range between any two.
[0093] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present application are described in detail as follows:
[0094] Example 1
[0095] This embodiment provides a method for preparing a battery, comprising the following steps:
[0096] (I) Preparation of positive electrode sheet:
[0097] (11) mixing the active material, the conductive agent, the gelling agent, the initiator and the first solvent at an ambient temperature of 25° C. and an ambient humidity of 10% to obtain a positive electrode slurry;
[0098] Among them, the gelling agent includes a polymer monomer, a cross-linking agent and a plasticizer. The polymer monomer is poly (ethylene glycol) diacrylate, the cross-linking agent is pentaerythritol tetraacrylate, the plasticizer is methylglutaronitrile, the active substance is lithium nickel cobalt manganese oxide, the conductive agent is carbon black, the initiator is N,N-azobisisobutyronitrile, the first solvent is N-methylpyrrolidone, the mass ratio between the active substance, the conductive agent, the gelling agent, the initiator and the solvent is 45:1.5:5:0.15:60, and the mass ratio between the polymer monomer, the cross-linking agent and the plasticizer is 70:20:10.
[0099] (12) The positive electrode slurry was coated on an aluminum foil by an extrusion coater and heated and cured at 85° C. for 1 h to obtain a positive electrode sheet having a thickness of 250 μm.
[0100] (II) Preparation of negative electrode sheet:
[0101] (21) mixing the active material, the conductive agent, the gelling agent, the initiator and the first solvent at an ambient temperature of 25° C. and an ambient humidity of 10% to obtain a negative electrode slurry;
[0102] Among them, the gelling agent includes a polymer monomer, a cross-linking agent and a plasticizer, the polymer monomer is poly (ethylene glycol) diacrylate, the cross-linking agent is pentaerythritol tetraacrylate, the plasticizer is methylglutaronitrile, the active substance is graphite, the conductive agent is carbon black, the initiator is N,N-azobisisobutyronitrile, the solvent is N-methylpyrrolidone, the mass ratio between the active substance, the conductive agent, the gelling agent, the initiator and the solvent is 45:1.5:5:0.15:60, and the mass ratio between the polymer monomer, the cross-linking agent and the plasticizer is 70:20:10.
[0103] (22) The negative electrode slurry was coated on a copper foil by an extrusion coater and heated and cured at 85° C. for 1 h to obtain a negative electrode sheet. The thickness of the negative electrode sheet was 100 μm.
[0104] (III) Battery assembly:
[0105] (31) The positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence and assembled to obtain a battery cell.
[0106] (32) The battery cell is placed in an aluminum battery shell, and then an electrolyte is injected and sealed to obtain a lithium-ion battery; wherein the mass percentage of the electrolyte in the lithium-ion battery is 15%, the electrolyte comprises a second solvent, a lithium salt and an additive, the second solvent is vinyl methyl carbonate, the lithium salt is lithium hexafluorophosphate, the additive is vinylene carbonate, the molar concentration of the lithium salt in the electrolyte is 1.5 mol / L, the mass percentage of the second solvent in the electrolyte is 75%, the mass percentage of the lithium salt in the electrolyte is 20%, and the mass percentage of the additive in the electrolyte is 5%.
[0107] Example 2
[0108] The difference between Example 2 and Example 1 is:
[0109] In step (11), the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 50:3:0.5:0.3:70, the mass ratio of the polymer monomer, the crosslinking agent and the plasticizer is 20:50:20, and the rest is the same as in Example 1.
[0110] Example 3
[0111] The difference between Example 3 and Example 1 is:
[0112] In step (11), the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 35:0.05:10:0.005:35, the mass ratio of the polymer monomer, the crosslinking agent and the plasticizer is 90:5:1, and the rest is the same as in Example 1.
[0113] Example 4
[0114] The difference between Example 4 and Example 1 is:
[0115] The polymer monomer in step (11) is polyacrylonitrile, and the rest is the same as in Example 1.
[0116] Example 5
[0117] The difference between Example 5 and Example 1 is:
[0118] The active material in step (11) is lithium cobalt oxide, and the rest is the same as in Example 1.
[0119] Example 6
[0120] The difference between Example 6 and Example 1 is:
[0121] In step (12), the temperature for heating and curing is 60° C., and the rest is the same as in Example 1.
[0122] Example 7
[0123] The difference between Example 7 and Example 1 is:
[0124] In step (12), the temperature for heating and curing is 150° C., and the rest is the same as in Example 1.
[0125] Example 8
[0126] The difference between Example 8 and Example 1 is:
[0127] In step (21), the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 50:3:0.5:0.3:70, the mass ratio of the polymer monomer, the crosslinking agent and the plasticizer is 20:50:20, and the rest is the same as in Example 1.
[0128] Example 9
[0129] The difference between Example 9 and Example 1 is:
[0130] In step (21), the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 35:0.05:10:0.005:35, the mass ratio of the polymer monomer, the crosslinking agent and the plasticizer is 90:5:1, and the rest is the same as in Example 1.
[0131] Example 10
[0132] The difference between Example 10 and Example 1 is:
[0133] In step (21), the polymer monomer is vinyl ethylene carbonate, and the rest is the same as in Example 1.
[0134] Embodiment 11
[0135] The difference between Example 11 and Example 1 is that:
[0136] In step (21), the active material is carbon nanotubes and the rest is the same as in Example 1.
[0137] Example 12
[0138] The difference between Example 12 and Example 1 is:
[0139] In step (22), the temperature for heating and curing is 60°C, and the rest is the same as in Example 1.
[0140] Example 13
[0141] The difference between Example 13 and Example 1 is that:
[0142] In step (22), the temperature for heating and curing is 150°C, and the rest is the same as in Example 1.
[0143] Embodiment 14
[0144] The difference between Example 14 and Example 1 is that:
[0145] In step (11), the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 35:0.05:20:0.005:35, the mass ratio of the polymer monomer, the crosslinking agent and the plasticizer is 90:5:1, and the rest is the same as in Example 1.
[0146] Embodiment 15
[0147] The difference between Example 15 and Example 1 is that:
[0148] In step (11), the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 50:3:0.3:0.3:70, the mass ratio of the polymer monomer, the crosslinking agent and the plasticizer is 20:50:20, and the rest is the same as in Example 1.
[0149] Example 16
[0150] Example 16
[0151] The difference from Example 1 is:
[0152] In step (12), the temperature for heating and curing is 50° C., and the rest is the same as in Example 1.
[0153] Embodiment 17
[0154] The difference between Example 17 and Example 1 is that:
[0155] In step (12), the temperature for heating and curing is 180°C, and the rest is the same as in Example 1.
[0156] Embodiment 18
[0157] The difference between Example 18 and Example 1 is that:
[0158] In step (21), the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 35:0.05:20:0.005:35, the mass ratio of the polymer monomer, the crosslinking agent and the plasticizer is 90:5:1, and the rest is the same as in Example 1.
[0159] Embodiment 19
[0160] The difference between Example 19 and Example 1 is that:
[0161] In step (21), the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 50:3:0.3:0.3:70, the mass ratio of the polymer monomer, the crosslinking agent and the plasticizer is 20:50:20, and the rest is the same as in Example 1.
[0162] Embodiment 20
[0163] The difference between Example 20 and Example 1 is that:
[0164] In step (22), the temperature for heating and curing is 50°C, and the rest is the same as in Example 1.
[0165] Embodiment 21
[0166] The difference between Example 21 and Example 1 is that:
[0167] In step (22), the temperature for heating and curing is 180°C, and the rest is the same as in Example 1.
[0168] Comparative Example 1
[0169] The difference between Comparative Example 1 and Example 1 is:
[0170] Step (11) is: mixing the active material, the conductive agent, the gelling agent, the initiator and the first solvent at an ambient temperature of 25° C. and an ambient humidity of 10% to obtain a positive electrode slurry;
[0171] Among them, the active material is lithium nickel cobalt manganese oxide, the conductive agent is carbon black, the initiator is N,N-azobisisobutyronitrile, the first solvent is N-methylpyrrolidone, and the mass ratio between the active material, the conductive agent, the gelling agent, the initiator and the solvent is 35:0.5:0:0.02:62.48; the rest is the same as Example 1.
[0172] Comparative Example 2
[0173] The difference between Comparative Example 2 and Example 1 is:
[0174] Step (11) is: mixing the active material, the conductive agent, the binder, the initiator and the first solvent at an ambient temperature of 25° C. and an ambient humidity of 10% to obtain a positive electrode slurry;
[0175] Among them, the active material is lithium nickel cobalt manganese oxide, the conductive agent is carbon black, the initiator is N,N-azobisisobutyronitrile, the first solvent is N-methylpyrrolidone, the binder is carboxymethyl cellulose, and the mass ratio of the active material, the conductive agent, the binder, the initiator and the solvent is 35:0.5:2:0.02:62.48; the rest is the same as Example 1.
[0176] Comparative Example 3
[0177] The difference between Comparative Example 3 and Example 1 is:
[0178] Step (21) is: mixing the active material, the conductive agent, the gelling agent, the initiator and the first solvent at an ambient temperature of 25° C. and an ambient humidity of 10% to obtain a negative electrode slurry;
[0179] Among them, the active material is graphite, the conductive agent is carbon black, the initiator is N,N-azobisisobutyronitrile, the solvent is N-methylpyrrolidone, and the mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the solvent is 35:0.5:0:0.01:62.49; the rest is the same as Example 1.
[0180] Comparative Example 4
[0181] The difference between Comparative Example 4 and Example 1 is:
[0182] Step (21) is: mixing the active material, the conductive agent, the binder, the initiator and the first solvent at an ambient temperature of 25° C. and an ambient humidity of 10% to obtain a negative electrode slurry;
[0183] Among them, the active material is graphite, the conductive agent is carbon black, the initiator is N,N-azobisisobutyronitrile, the solvent is N-methylpyrrolidone, the binder is carboxymethyl cellulose, and the mass ratio of the active material, the conductive agent, the binder, the initiator and the solvent is 35:0.5:2:0.01:62.49; the rest is the same as Example 1.
[0184] Test Method
[0185] The electrochemical performance of the batteries obtained in Examples 1 to 21 and Comparative Examples 1 to 4 was tested, and the specific method is as follows:
[0186] (1) Cycling performance: Full battery test of lithium-ion batteries at 25°C with constant current and constant voltage charging and discharging at a current density of 1C, with a charge and discharge voltage window of 2.75V-4.2V.
[0187] (2) Rate performance: The lithium-ion battery is charged at a current density of 1C and discharged at a current density of 3C with a constant current and constant voltage for full battery testing. The charge and discharge voltage window is 2.75V-4.2V.
[0188] The test results are shown in Table 1 below:
[0189] Table 1
[0190]
[0191]
[0192] Based on the test results of the above-mentioned Examples 1 to 21 and Comparative Examples 1 to Comparative Examples 4, it can be seen that the lithium ion batteries prepared in Examples 1 to 21 have good rate performance and excellent cycle performance, which shows that when the electrode plate is prepared in the present application, the electrode active substance is directly in contact with the gelling agent, and when the polymer monomer is heated and cured to form a gel polymer, the gel polymer can wrap the active substance particles, and the active substance particles are directly in contact with the gel polymer and are uniformly dispersed in the gel polymer, which can improve the interface compatibility between the gel polymer and the electrode active substance, reduce the interface impedance between the gel polymer and the electrode active substance, improve the ion transfer efficiency, and improve the rate performance and cycle performance of the battery.
[0193] From the comparison between Examples 1 to 3 and Examples 14 and 15, it can be seen that when preparing the positive electrode sheet, controlling the content of the polymer monomer within an appropriate range can further ensure the rate performance, cycle performance and safety performance of the battery.
[0194] From the comparison of Example 1, Example 6, Example 7, Example 16 and Example 17, it can be seen that when preparing the positive electrode plate, controlling the heating and curing temperature within an appropriate range can further ensure the rate performance, cycle performance and safety performance of the battery.
[0195] From the comparison of Example 1, Example 8, Example 9, Example 18 and Example 19, it can be seen that when preparing the negative electrode plate, controlling the content of the polymer monomer within an appropriate range can further ensure the rate performance, cycle performance and safety performance of the battery.
[0196] From the comparison among Example 1, Example 12, Example 13, Example 20 and Example 21, it can be seen that when preparing the negative electrode plate, controlling the heating and curing temperature within an appropriate range can further ensure the rate performance, cycle performance and safety performance of the battery.
[0197] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing an electrode sheet, characterized in that: The method for preparing the electrode sheet comprises the following steps: Providing an electrode slurry, wherein the electrode slurry comprises an active material, a gelling agent and a first solvent, wherein the gelling agent comprises a polymer monomer; The electrode slurry is coated on a current collector and heated and cured to obtain the electrode plate.
2. The preparation method according to claim 1, characterized in that: The preparation method of the electrode slurry comprises the following steps: The active material, the gelling agent, the first solvent and other raw materials in the formulated amount are uniformly mixed to obtain the electrode slurry.
3. The preparation method according to claim 2, characterized in that: The mixing is stirring mixing, and / or the mixing environment temperature is 20° C.-30° C., and / or the mixing environment humidity is less than or equal to 10%, and / or the mixing time is 4h-20h; and / or The electrode slurry is coated on the current collector by an extrusion coater; and / or The temperature of the heating and curing is 60° C.-150° C., and / or the time of the heating and curing is 20 min-60 min.
4. The preparation method according to claim 2 or 3, characterized in that: The other raw materials include a conductive agent and an initiator; and / or The gelling agent further comprises a cross-linking agent and a plasticizer; and / or The electrode plate is a positive electrode plate, the active material includes at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt manganese oxide, and / or the current collector includes at least one of aluminum foil and stainless steel foil; and / or The electrode plate is a negative electrode plate, the active material includes at least one of graphite, silicon carbon, lithium carbonate, and carbon nanotubes, and / or the current collector includes at least one of copper foil and stainless steel foil; and / or The polymer monomer comprises at least one of polyethylene glycol dimethacrylate, triethylene glycol dimethacrylate, poly(ethylene glycol) diacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, ethylene glycol phenyl ether acrylate, methyl methacrylate, vinyl ethylene carbonate, poly(ethylene glycol), polyvinylidene fluoride, poly(vinylidene fluoride-co-hexafluoropropylene), and polyacrylonitrile; and / or The first solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethylacetamide, acetonitrile, dimethyl sulfoxide, and tetrahydrofuran.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the active material, the conductive agent, the gelling agent, the initiator and the first solvent is (35-50): (0.05-3): (0.5-10): (0.005-0.3): (35-70); and / or The mass ratio of the polymer monomer, the cross-linking agent and the plasticizer is (20-90): (5-50): (1-20).
6. The preparation method according to claim 4, characterized in that: The conductive agent includes at least one of carbon black, carbon nanotubes, and graphene; and / or The initiator comprises at least one of N,N-azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, diethylhexyl oxydicarbonate, benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate; and / or The cross-linking agent comprises at least one of pentaerythritol tetraacrylate, polyethylene glycol dimethacrylate, triethylene glycol dimethacrylate, poly(ethylene glycol) diacrylate, trimethylol propane ethoxylate triacrylate, propoxylated trimethylol propane triacrylate, trimethylol propane trimethacrylate, and di(trimethylol propane) tetraacrylate; and / or The plasticizer includes at least one of succinonitrile, adiponitrile, methylglutaronitrile, 3-methoxypropionitrile, vinylene carbonate, 4-vinyl-1,3-dioxolane-2-one, silicon dioxide and titanium dioxide.
7. An electrode plate, characterized in that: The electrode plate is prepared by the preparation method according to any one of claims 1 to 6.
8. The electrode plate according to claim 7, characterized in that: The electrode plate comprises a current collector and a composite gel layer, wherein the composite gel layer is formed on the surface of the current collector by in-situ polymerization of polymer monomers, wherein the composite gel layer comprises a gel polymer and an active substance dispersed in the gel polymer; and / or The thickness of the electrode plate is 20 μm-500 μm; and / or The electrode plate is a positive electrode plate, the active material includes at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt manganese oxide, and / or the current collector includes at least one of aluminum foil and stainless steel foil; and / or The electrode plate is a negative electrode plate, the active material includes at least one of graphite, silicon carbon, lithium carbonate, and carbon nanotubes, and / or the current collector includes at least one of copper foil and stainless steel foil.
9. A lithium ion battery, characterized in that: The invention comprises the electrode plate as claimed in claim 7 or 8 or the electrode plate made by the preparation method as claimed in any one of claims 1 to 6.
10. A method for preparing a lithium ion battery, characterized in that: The following steps are involved: Providing an electrode sheet, a separator and an electrolyte, wherein the electrode sheet is prepared by the preparation method according to any one of claims 1 to 6; The electrode plates and the separator are stacked or wound to obtain a battery cell; The battery cell is installed in a battery casing, the electrolyte is injected into the battery cell, and the battery cell is sealed to obtain the lithium ion battery.
11. The method for preparing a lithium ion battery according to claim 10, characterized in that: The mass percentage of the electrolyte in the lithium ion battery is 10%-18%; and / or The electrolyte comprises a second solvent, a lithium salt and an additive; and / or The electrode plates include a positive electrode plate and a negative electrode plate. The positive electrode plate, the separator and the negative electrode plate are stacked in sequence to obtain the battery cell.
12. The method for preparing a lithium ion battery according to claim 11, characterized in that: The second solvent comprises at least one of ethylene carbonate, propylene carbonate, vinyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dimethyltetrahydrofuran, tetrahydrofuran, 1,2-dimethoxyethane, ethyl acetate, methyl acetate, methyl formate, ethyl formate, propyl formate, isopropyl formate, and 1,4-butyrolactone; and / or The lithium salt comprises at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluorooxalatophosphate, lithium bis(fluorobis(oxalatophosphate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, and lithium bis(oxalatoborate); and / or The additive comprises at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, vinyl sulfite, polyether sulfone, vinyl sulfate, and propenyl-1,3-sultone; and / or The molar concentration of the lithium salt in the electrolyte is 1.2 mol / L-2.0 mol / L; and / or The mass percentage of the second solvent in the electrolyte is 50%-75%; and / or The mass percentage of the lithium salt in the electrolyte is 10%-35%; and / or The mass percentage of the additive in the electrolyte is 1%-15%.
Citation Information
Cited By
Method for synergistically improving resistivity of lithium iron phosphate pole piece based on moisture pre-regulation and low-temperature hot pressing
CN121687879A
Resin composition, pole piece, preparation method of pole piece, single battery, battery device and electric equipment
CN122278429A